Influence of mineral fertilizers on the chemical composition of japanese persimmon leaves cultivated in humid subtropical zone of Russia - T. D. Besedina; M. J. Omarov (Новые технологии, 2018)
The study of the mineral nutrition of Japanese Persimmon (Hiakume variety) on the basis of multifactorial experience has provided an opportunity to develop a vegetative diagnosis of its plantations humid subtropical conditions. The terms of diagnostics of the degree of provision of plants with food for operative correction of the yield and criteria for the provision with basic elements of nutrition (N, P, K, Ca, Mg) are established. It’s been determined that nitrogen in various ratios and interactions with phosphorus and potassium is a leading factor in nutrition.